Three hours in paris eaudiobook - Black, Cara (Kate Rees WWII, 2020)
In June of 1940, when Paris fell to the Nazis, Hitler spent a total of three hours in the City of Light—abruptly leaving, never to return. To this day, no one knows why. Kate Rees, a young American markswoman, has been recruited by British intelligence to drop into Paris with a dangerous assignment: assassinate the Führer. Wrecked by grief after a Luftwaffe bombing killed her husband and infant daughter, she is armed with a rifle, a vendetta, and a fierce resolve. But other than rushed and rudimentary instruction, she has no formal spy training. Thrust into the red-hot center of the war, a country girl from rural Oregon finds herself holding the fate of the world in her hands. When Kate misses her mark and the plan unravels, Kate is on the run for her life—all the time wrestling with the suspicion that the whole operation was a set-up. New York Times bestselling author Cara Black is at her best as she brings Occupation-era France to vivid life in this masterful, pulse-pounding story about one young woman with the temerity—and drive—to take on Hitler himself.